Optical proferties of PrSb₂ thin films of dark blue coloring - Jabua, Z.U.; Kupreishvili, I.L.; Gigineishvili, A.V. (Физическая инженерия поверхности, 2013)
A processes has been developed for the growth of thin crystalline PrSb₂ films different coloring by thermal evaporation using Pr and Sb separate sources. The room-temperature optical spectra (reflectivity, absorption coefficient, loss funqtion, real and imaginary parts of dielectric permittivity, optical conductivity) of PrSb₂ films dark blue coloring have been studied at phonon energy from 0.05 to 5.5 eV. The behavior and energy position of features in the spectra have been analyzed.